Renal Pelviceal Keratinizing Squamous Metaplasia with Sparing of Pyramidal Zones - Richard H. Siderits; Jared Fingerman; Anup Hazra; Cheryl Rimmer; Marc Colaco; Nagy Mikhail; Cristian Ardeleanu; Peter M. Mazari (Case Reports in Urology)
Metaplastic changes in the urothelium of the upper urinary tract are relatively infrequent. Metaplasia may present as either squamous or less often glandular differentiation. The process may be associated with chronic inflammation or associated chronic infections. There may be malignant transformation to either squamous cell carcinoma or adenocarcinoma. The demarcation of the metaplastic process in the minor calyces has not been well documented to date. We report the case of a 74-year-old female patient who presented with a history of chronic renal disease and acute pyohydronephrosis. The patient underwent a nephroureterectomy which revealed keratinizing desquamative squamous metaplasia throughout the renal pelvis and upper urinary tract with abrupt termination of metaplasia at the junction of the renal pelvis and the minor calyx (pyramidal zone). Immunohistochemical evaluation documents metaplastic urothelium stained positive for CK5, before converting sharply to simple cuboidal epithelium in the minor calyx (pyramidal zones) which stained positive CK7. At the junction of the metaplastic components and low cuboidal lined minor calyceal surfaces, the underlying stroma showed loss of ureteral muscularis mucosa with transition to renal parenchymal type stroma. We believe that this observation is unique and potentially relevant to the etiology and pathophysiology of pelviceal metaplasia.